2016
DOI: 10.1007/s00192-016-3031-7
|View full text |Cite
|
Sign up to set email alerts
|

Methods for a multicenter randomized trial for mixed urinary incontinence: rationale and patient-centeredness of the ESTEEM trial

Abstract: Introduction Mixed urinary incontinence (MUI) can be a challenging condition to manage. We describe the protocol design and rationale for the Effects of Surgical Treatment Enhanced with Exercise for Mixed Urinary Incontinence (ESTEEM) trial, designed to compare a combined conservative and surgical treatment approach versus surgery alone for improving patient-centered MUI outcomes at 12 months. Methods ESTEEM is a multi-site, prospective, randomized trial of female participants with MUI randomized to a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Furthermore, we discouraged participants from engaging in vaginal intercourse/douching/using vaginal sprays or wipes for 48 hours prior to study visits and specimens were collected at least 48 hours following cessation of menses. MUI participants consisted of a subset of women enrolled in a randomized trial of MUI treatment comparing efficacy of mid-urethral sling (MUS) surgery alone to MUS surgery and behavioral therapy (NCT# 01959347) [2]. For this supplementary study, we also recruited controls who were of similar age as the MUI cases, as described in the methods paper [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we discouraged participants from engaging in vaginal intercourse/douching/using vaginal sprays or wipes for 48 hours prior to study visits and specimens were collected at least 48 hours following cessation of menses. MUI participants consisted of a subset of women enrolled in a randomized trial of MUI treatment comparing efficacy of mid-urethral sling (MUS) surgery alone to MUS surgery and behavioral therapy (NCT# 01959347) [2]. For this supplementary study, we also recruited controls who were of similar age as the MUI cases, as described in the methods paper [6].…”
Section: Methodsmentioning
confidence: 99%
“…Women with MUI face a therapeutic dilemma because of the dual nature of their condition; treatment of stress urinary incontinence (SUI) symptoms may exacerbate urgency while treatment of urgency urinary incontinence (UUI) symptoms may worsen SUI. The study, Effects of Surgical Treatment Enhanced with Exercise for Mixed Urinary Incontinence (ESTEEM), was designed to compare stress, urgency and MUI symptom outcomes in an MUI population treated with surgery alone versus surgery and behavioral/pelvic floor therapy [2]. The ESTEEM study’s population provided a singular opportunity to evaluate the urinary microbiome as a biologically plausible contributor to MUI.…”
Section: Introductionmentioning
confidence: 99%
“…The ESTEEM trial methods have been published previously [11]. The ESTEEM parent trial enrolled women with MUI who reported at least “moderate bother” for both UUI and SUI components of the Urinary Distress Inventory (UDI) questionnaire [12].…”
Section: Methodsmentioning
confidence: 99%
“…The ESTEEM trial was designed to compare urinary incontinence symptom outcomes in women randomized to a standardized perioperative behavioral/pelvic floor exercise intervention plus midurethral sling versus midurethral sling alone [11]. While ESTEEM interventions are aligned with traditional treatment approaches to SUI and UUI, the ESTEEM population provides a unique opportunity to explore alternative hypotheses regarding the etiology of MUI as well as MUI treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…The ESTEEM trial was designed to compare a combined conservative and surgical treatment approach versus surgery alone for improving patient‐centered MUI outcomes at 12 months. It is a multi‐site, prospective randomized trial of female patients with MUI randomized to a standardized perioperative behavioral/pelvic floor exercise intervention plus MUS versus MUS alone . Sung and colleagues describe the inclusion and exclusion criteria and primary and secondary outcomes .…”
Section: Introductionmentioning
confidence: 99%